STABILITAS SAMPAN TERBUAT DARI EMBER CAT BEKAS DENGAN BILGE KEEL PADA SUDUT 30 DAN 45 DERAJAT - Muhammad Agam Thahir; Budhi H. Iskandar; Mohammad Imron (Jurnal Teknologi Perikanan dan Kelautan, 2013)
Used-paint-buckets can be used as an alternative material instead of wood or fibreglass in contructing a canoe. Its light weight and easy to roll, even in relatively calm water, showing of the low stability. In order to increase its stability, bilge keels were applied in this canoe. The purpose of this study is to obtain the impact of bilge keels application at different angles in order to increase stability. The dimension of the canoe was: the length (LOA) 3.15 m; width (B) 0.64 m; and depth (D) 0.30 m. Numerical simulation method to obtain the value of some stability parameter and seakeeping (pitching, heaving, and rolling) was used in this study. For the wave factor, JONSWAP wave spectrum was used as an input in this numerical simulation. The analysis result showed that there were differences in the stability, indicated by the value of righting arm on the bilge keel with 30 and 45 degree as much as 0.001 m. Bilge keel with an angle of 30 degrees give better stability value compare to 45 degrees. From the analysis of the response amplitude operator (RAO) showed that the rolling, pithcing and heaving motion of the canoe was remain in the normal.